Age-dependent behavioral and synaptic dysfunction impairment are improved with long-term andrographolide administration in long-lived female degus (Octodon degus) - Oliva, Carolina A.; Rivera, Daniela S.; Torres, Angie K.; Lindsay, Carolina B.; Tapia Rojas, Cheril.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (MDPI, 2023)
In Octodon degus, the aging process is not equivalent between sexes and worsens for females. To determine the beginning of detrimental features in females and the ways in which to improve them, we compared adult females (36 months old) and aged females (72 months old) treated with Andrographolide (ANDRO), the primary ingredient in Andrographis paniculata. Our behavioral data demonstrated that age does not affect recognition memory and preference for novel experiences, but ANDRO increases these at both ages. Sociability was also not affected by age; however, social recognition and long-term memory were lower in the aged females than adults but were restored with ANDRO. The synaptic physiology data from brain slices showed that adults have more basal synaptic efficiency than aged degus; however, ANDRO reduced basal activity in adults, while it increased long-term potentiation (LTP). Instead, ANDRO increased the basal synaptic activity and LTP in aged females. Age-dependent changes were also observed in synaptic proteins, where aged females have higher synaptotagmin (SYT) and lower postsynaptic density protein-95 (PSD95) levels than adults. ANDRO increased the N-methyl D-aspartate receptor subtype 2B (NR2B) at both ages and the PSD95 and Homer1 only in the aged. Thus, females exposed to long-term ANDRO administration show improved complex behaviors related to age-detrimental effects, modulating mechanisms of synaptic transmission, and proteins.
Keywords: Octodon degus; Andrographolide; Synaptic plasticity; Envejecimiento; Memoria colectiva; Transmisión sináptica